2008
DOI: 10.1007/s10336-007-0262-x
|View full text |Cite
|
Sign up to set email alerts
|

Avian species richness and abundance at Lake Constance: diverging long-term trends in Passerines and Nonpasserines

Abstract: In Central Europe, massive losses in species richness of breeding birds have been documented in the last decades, but the question arises whether species richness is currently still decreasing or again increasing due to conservation efforts. In this study, we investigated regional and local species richness as well as mean number of breeding pairs and mean biomass per tetrad over a period of some 20 years at Lake Constance. Three quantitative censuses of 303 tetrads (2 9 2 km 2 ) repeated at 10-year intervals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…This result is consistent with the observations of climate change impact on bird species (Julliard et al 2004;Jiguet et al 2007;Bauer et al 2008). It also corroborates predictions of future breeding bird distribution patterns modeled under various scenarios of climatic warming (Huntley et al 2007).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This result is consistent with the observations of climate change impact on bird species (Julliard et al 2004;Jiguet et al 2007;Bauer et al 2008). It also corroborates predictions of future breeding bird distribution patterns modeled under various scenarios of climatic warming (Huntley et al 2007).…”
Section: Discussionsupporting
confidence: 92%
“…First, landscape changes, such as the loss of extensively cultivated farmland because of agricultural intensification or land abandonment followed by forest spread, should reduce the distribution of farmland birds and increase the distribution of forest species (Lenzen et al 2008;Reif et al 2008a;Orłowski and Ławniczak 2009). Second, the increase in the average annual temperature should have a positive effect on the distribution of south European species and a negative impact on the north European ones (Bauer et al 2008;Reif et al 2008b). Third, global warming, along with the degradation of wintering habitats, should lead to an increase in the distribution of resident species and to a decrease of migrants (Schaefer et al 2008).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…K-selected species, therefore, will be more threatened under conditions of recent environmental perturbation than species with faster life histories ('r-selected' species). Finally, recent studies have indicated that climate change has had a negative impact upon reproduction in long-distance migratory species, species occupying cold-climate niches and species that breed late in the breeding season (Bauer, Lemoine & Peintinger, 2008;Reif et al, 2008;Schaefer, Jetz & Böhning-Gaese, 2008;Salido et al, 2012). As such, species are likely to be more affected by a phenological mismatch between time of breeding and availability of food; they are more likely to be threatened than, for example, southern European species and species that start breeding earlier (see Both et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Avian diversity of farmland bird species has declined markedly in European agricultural landscapes during the recent decades (Böhning-Gaese & Bauer 1996, Pain & Pienowski 1997, BirdLife International 2004, Newton 2004, PECBM 2009. At Lake Constance (SW-Germany, W-Austria, N-Switzerland), a mosaic of forests, arable fields, orchards, fruit plantations and wetlands, it was found that the species richness and number of breeding pairs showed a strong decline from 1980 to 2000 (Bauer et al 2008). However, the changes in species richness differed markedly between non-passerine birds that remained constant from 1980 to 1990, and even increased between 1990 and 2000, and passerine birds that decreased in both periods.…”
Section: Introductionmentioning
confidence: 99%